2019
DOI: 10.1111/imb.12616
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the DNA methyltransferase 1 associated protein 1 (DMAP1) gene in the invasive ladybird Harmonia axyridis implies a role of the DNA methyltransferase 1‐DMAP1 complex in female fecundity

Abstract: The invasive harlequin ladybird Harmonia axyridis is a textbook example of polymorphism and polyphenism as the temperature during egg development determines the frequency of melanic morphs and the number and size of black spots in nonmelanic morphs. Recent concepts in evolutionary biology suggest that epigenetic mechanisms can translate environmental stimuli into heritable phenotypic changes. To investigate whether epigenetic mechanisms influence the penetrance and expressivity of colour morphs in H. axyridis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…For instance, a recent study found that gene knockdown of Dnmt1 and methyl-DNA-binding protein 2/3 ( MBD2/3 ) - a gene involved in gene body methylation in insects - and methylation inhibition by 5-aza-2’-deoxycytidine (a pharmaceutical alternative to Zeb) impaired ovary development and reduced fecundity and hatch rates in developing silkworm ( Bombyx mori ), tobacco cutworm ( Spodoptera litura ) and migratory locust ( Locusta migratoria ), suggesting intragenic DNA methylation regulates insect reproduction [56]. Silencing the Dnmt1 associated protein 1 ( DMAP1 ) gene severely reduced fecundity and offspring survival in the harlequin ladybird ( Harmonia axyridis ), suggesting a role of the DNMT-DMAP1 complex in life history traits in H. axyridis [23]. Similarly, Dnmt silencing reduced the number of offspring produced in the brown plant hopper ( Nilaparvata lugens ) [21] and reduced egg production and embryo viability in the large milkweed bug ( Oncopeltus fasciatus ) [22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, a recent study found that gene knockdown of Dnmt1 and methyl-DNA-binding protein 2/3 ( MBD2/3 ) - a gene involved in gene body methylation in insects - and methylation inhibition by 5-aza-2’-deoxycytidine (a pharmaceutical alternative to Zeb) impaired ovary development and reduced fecundity and hatch rates in developing silkworm ( Bombyx mori ), tobacco cutworm ( Spodoptera litura ) and migratory locust ( Locusta migratoria ), suggesting intragenic DNA methylation regulates insect reproduction [56]. Silencing the Dnmt1 associated protein 1 ( DMAP1 ) gene severely reduced fecundity and offspring survival in the harlequin ladybird ( Harmonia axyridis ), suggesting a role of the DNMT-DMAP1 complex in life history traits in H. axyridis [23]. Similarly, Dnmt silencing reduced the number of offspring produced in the brown plant hopper ( Nilaparvata lugens ) [21] and reduced egg production and embryo viability in the large milkweed bug ( Oncopeltus fasciatus ) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature induced changes in Dnmt expression or DNA methylation levels have previously been found in many insect species ( [20] and references therein), and previous studies have further identified a role for DNA methylation in insect life history and fitness [21][22][23]. Here, in an insect model species, we evaluate temperature dependence of DNA methylation, and we further manipulate epigenetic potential to assess downstream consequences for temperature-mediated plasticity in life history traits.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations